Causes and Consequences of Cyberbullying Against Women in Bangladesh: A Comprehensive Study. - Amin, Ruhul (Salasika, 2023)
Cyberbullying has emerged as a significant threat to women in Bangladesh, with the digital realm becoming a new battleground for harassment and intimidation. With the rapid advancement and widespread integration of information and communication technology (ICT), a unique form of wrongdoing has emerged within the virtual realm of the internet. This phenomenon, commonly referred to as cyberbullying, has gained widespread prevalence, particularly on social media platforms, where individuals readily participate in activities such as verbal abuse, dissemination of false information, and propagation of hate speech. In the context of Digital Bangladesh, where the use of the internet and social media is experiencing rapid growth, cyberbullying has become a frequent and noteworthy occurrence. The consequences of cyberbullying are enduring and multifaceted. This article seeks to explore the global issue of cyberbullying, with a specific focus on the situation in Digital Bangladesh, particularly concerning women. The primary aim of this article is to scrutinize cyberbullying, comprehending its underlying causes and investigating its widespread consequences. Additionally, the article directs attention to the legislative measures in Bangladesh designed to address this global issue and examines how the country is addressing cyberbullying in the current and forthcoming periods. The insights derived from this study can serve as a valuable reference for young individuals, educators, lawmakers, advocates, and concerned citizens, offering them a comprehensive understanding of the prevailing cyberbullying landscape in Digital Bangladesh.